An ecstatic assault? - Abd Razak, Dzulkifli (1996)
ECSTASY, A COMMONLY understood noun, means "overpowering emotion, especially delight". It has recently acquired quite another meaning in this country. Of late, Ecstasy has come to be reffered to as a kind of potent drug abused by a segment of the population. This is causing a great deal of concern. Ecstasy refers to the street name of a chemical constituent 3,4 methylenedioxymeth amphetamine or MDMA for short. It has also been reffered to among others by names such as XTC, ADAM, AKA or simply "E." The pills so far identified are pinkish or offwhite in colour. However, the names and appearances tend to change from time to time to avoid detection, thus complicating the situation further. In its pure form, it is a white crystalline powder.